Employing a failure criterion with interaction terms to simulate the progressive failure of carbon-epoxy laminates - Mahmud, Jamaluddin; Ismail, Ahmad Faris; Pervez, Tasneem (The Institution of Engineers, 2005)
A failure criterion with the existence of coupling terms is employed to investigate the progressive failure in anisotropic laminated carbon-epoxy plates. The criterion is employed because it is developed recently. Moreover, the criterion allows interaction between fiber and matrix properties. This paper is aimed to investigate the contribution of the coupling terms and thus, to simulate the progressive failure of the carbon-epoxy plates. A mathematical model and computational model are presented for the analysis. The deformation of the plates is predicted based on higher order shear deformation theory. Variation of material properties through thickness is used and accommodated by a discrete layer approach. A program based on finite element method is developed to determine the lamina stresses. Stresses calculated are used in the present failure model to determine the first ply failure and last ply failure, by progressively reducing the stiffness of the laminas. Finally, the first ply failure and last ply failure results are used to determine the lower and upper bounds within which the true load carrying capacity lies. The numerical results obtained show some improvement compared to other failure criteria.